2022
DOI: 10.4155/bio-2022-0155
|View full text |Cite
|
Sign up to set email alerts
|

Application of a new volumetric microsampling device for quantitative bioanalysis of immunosuppression

Abstract: Background: Volumetric absorptive microsampling may reduce the blood collection burden associated with therapeutic drug monitoring of immunosuppression to prevent organ transplant rejection. This work describes the development of a laboratory and analytical technique for quantifying tacrolimus and mycophenolic acid (MPA) from the Tasso-M20™ in human whole blood using bead-based impact-assisted extraction. Results: The sampled blood volume was accurate with estimated volumes within <2% of the expected 20 μl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 63 Additionally, Leino et al also validated the application of TASSO‐M20 for the quantitative bioanalysis of tacrolimus and mycophenolic acid. 113 Although these studies demonstrated the feasibility of microsampling in TDM of IMS, results from a proficiency testing pilot for IMS microsampling assays when compared to whole blood methods showed great interlaboratory variation. Since the results influence clinical decision‐making, harmonization and standardization are thus necessary before microsampling techniques can be implemented in patient care.…”
Section: Applicationsmentioning
confidence: 97%
See 3 more Smart Citations
“… 63 Additionally, Leino et al also validated the application of TASSO‐M20 for the quantitative bioanalysis of tacrolimus and mycophenolic acid. 113 Although these studies demonstrated the feasibility of microsampling in TDM of IMS, results from a proficiency testing pilot for IMS microsampling assays when compared to whole blood methods showed great interlaboratory variation. Since the results influence clinical decision‐making, harmonization and standardization are thus necessary before microsampling techniques can be implemented in patient care.…”
Section: Applicationsmentioning
confidence: 97%
“…111 Microsampling has been extensively studied for the determination of tacrolimus and mycophenolic acid, two of the most commonly prescribed IMS used to prevent organ rejection in recipients of solid organ transplants. 32,63,64,112,113 samples due to poor sample quality) and costs (7 times lower than Mitra device). 32,64 Additionally, use of non-contact Hct prediction strategies such as NIR and UV/VIS spectroscopy coupled to an automated DBS workflow was found to adequately correct for Hct effect in determining IMS concentrations.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the commercially available PCS devices, the Mitra® device by Neoteryx and Tasso‐M20 by Tasso are most frequently utilized. These two devices with volumetric absorptive microsampler (VAMS) technology have been widely documented in the literatures by both pharmaceutical companies and academic institutions for their successful application in clinical trials, ensuring the acquisition of high‐quality data from samples collected using Mitra® 14–19 and Tasso‐M20 20–22 devices. In addition, TAP® (Touch Activated Phlebotomy) device by YourBio Health, 23 hemaPEN® by Neoteryx, 24 and Capitainer®B by Capitainer 25 have all been successfully applied in clinical trials.…”
Section: Advancing Clinical Studies With Pcsmentioning
confidence: 99%